Dieulafoy lesion of the gallbladder presenting with bleeding and a pseudo-mirizzi syndrome: A case report and review of the literature. (2016) - Stanes, Aaron; Mackay, Sean
Highlights: The gallbladder is a rare source of severe gastrointestinal bleeding. Dieulafoy lesions can occur within the gallbladder. Cholecystectomy is a management option for gallbladder dieulafoy lesions. Extrinsic compression by a distended gallbladder may cause obstructive jaundice. Abstract: Introduction: Gastrointestinal bleeding can have significant morbidity and mortality. Pathological processes that cause it are diverse, and timely investigation and management are vital. Dieulafoy lesions are a rare cause of gastrointestinal bleeding and here we describe a case of a gallbladder dieulafoy lesion causing gastrointestinal bleeding. Presentation of case: Recently discharged from hospital following an open anterior resection and loop ileostomy for diverticular disease, an 84-year-old female re-presented with lower abdominal pain associated with jaundice and lymphocytosis. Imaging demonstrated two possible rectal stump collections (treated with antibiotics), and heterogeneous material in the gallbladder. The patient deteriorated, developing melena, coffee ground vomitus and right upper quadrant pain. Investigation sourced the bleeding to the gallbladder that resolved following cholecystectomy, and histopathology was consistent with a dieulafoy lesion. The patient made a full recovery. Discussion: Dieulafoy lesions have rarely been reported in the gallbladder, and as such can be an occult source of massive gastrointestinal bleeding. It should be considered where gastrointestinal bleeding accompanies jaundice and abdominal pain. Conclusion: This case highlights that dieulafoy lesions can occur in the gallbladder. Massive gastrointestinal bleeding can occur within the gallbladder, and a gallbladder dieulafoy lesion should be considered as a potential cause of such, especially when a source has not been identified on endoscopy. It also demonstrates the effectiveness of cholecystectomy as a definitive management strategy.